MERANCANG SISTEM UNTUK MEMPEROLEH SISTEM YANG INTERAKTIF: TINJAUAN LITERATUR YANG SISTEMATIS - Bintana, Rizqa Raaiqa; Lestari, Dewi; Noverina, Yolla (ScientiCO : Computer Science and Informatics Journal, 2020)
Structural design quality is an important driver of the overall quality of software applications. It is widely recognized in the literature that a low design quality of software negatively inï¬‚uences a number of external quality variables in the medium term, such as bug-proneness, usability, and reliability, which can be directly perceived by users. The use of design models when designing software, in particular by using the UML, has held the promise of quality improvements, automated code generation, improved problem solving and design capabilities, and in general improved productivity in software development. The conceptual modeling of classical systems is patially solved using a language such as UML. Visualizing relations of software entities often helped developers or programmer understand what he wants develop. Interactive visualizations can naturally support explorations of structures and convey evolution tendencies. Visual tool allows exploring software designs that evolve over time.